2016
DOI: 10.1536/ihj.15-322
|View full text |Cite
|
Sign up to set email alerts
|

Time Rate of Blood Pressure Variation Is Associated With Endothelial Function in Patients With Metabolic Syndrome

Abstract: SummaryThe time rate of blood pressure (BP) variation indicates the speed of BP fluctuations. Previous studies have demonstrated that the time rate of BP variation was associated with target organ damage. However, the association between time rate of BP variation and endothelial function has not been evaluated.24-hour ambulatory blood pressure monitoring (ABPM) was performed in 61 patients with metabolic syndrome. Time rate of BP variation was calculated from BP recordings of ABPM. Endothelial function was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…8) It has been reported that mild glucose intolerance, 23) excessive salt intake, 24) lack of regular exercise, 25) estrogen deficiency, 26) and depression status 27) in addition to conventional CVD risk factors lead to endothelial dysfunction. 28) In addition, those factors might impair the cognitive function through the disturbance of the cerebral microcirculation via decreased nitric oxide synthesis, prostacyclin, tissue plasminogen activator, and shear stress. 29,30) In particu-lar, those factors might interactively deteriorate the status of the endothelial function in CVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…8) It has been reported that mild glucose intolerance, 23) excessive salt intake, 24) lack of regular exercise, 25) estrogen deficiency, 26) and depression status 27) in addition to conventional CVD risk factors lead to endothelial dysfunction. 28) In addition, those factors might impair the cognitive function through the disturbance of the cerebral microcirculation via decreased nitric oxide synthesis, prostacyclin, tissue plasminogen activator, and shear stress. 29,30) In particu-lar, those factors might interactively deteriorate the status of the endothelial function in CVD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Absence of the normal nocturnal fall in SBP is associated with increased morbidity and mortality, and poses a substantial risk even after antihypertensive treatment. [17][18][19] Studies have reported the association of non-dipper pattern of BP with carotid intima-media thickness (CIMT), which was assessed by B-mode ultrasound and widely performed to evaluate the risk and prognosis of cardiovascular diseases. 20,21) Patients with a non-dipper pattern have more target-organ damage induced by hypertension, such as left ventricular hypertrophy, microalbuminuria, and reduced arterial compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial function was evaluated by the RHI, 7) which is the ratio of reactive hyperemia-stimulated vasodilation at the fingertip immediately after releasing a clamp of the brachial artery to that measured at the contralateral fingertip without clamping of the brachial artery using the Endo-PAT2000 (Itamar Medical, Caesarea, Israel). Increased blood flow during reactive hyperemia is mainly mediated by NO.…”
Section: Methodsmentioning
confidence: 99%